Characterizing burnout and resilience among nurses: A latent profile analysis of emotional exhaustion, emotional thriving and emotional recovery - Lesley C. Rink; Susan G. Silva; Kathryn C. Adair; Tolu O. Oyesanya; Janice C. Humphreys; John Bryan Sexton (Wiley, 2023)
Abstract Aims To identify subgroups of nurses with distinct profiles of burnout (emotional exhaustion) and resilience (emotional thriving and emotional recovery) and describe nurse characteristics associated with each profile. Design Cross‐sectional, correlational design. Methods Data were collected via electronic survey from 2018 to 2019. Latent profile analysis was used to identify subgroups of nurses with distinct profiles of emotional exhaustion, emotional thriving and emotional recovery, with each measured on a 0-100 scale. Bivariate statistics were used to determine profile differences in nurse sociodemographic, professional and psychological characteristics. Results Four distinct profile subgroups were identified: (1) "exhausted" (14% with very high emotional exhaustion, low emotional thriving and moderate emotional recovery), (2) "exhausted with thriving" (6% with high emotional exhaustion, moderate‐high emotional thriving and low emotional recovery), (3) "exhausted with thriving and recovery" (52% with moderate‐high emotional exhaustion, emotional thriving and emotional recovery), and (4) "thriving and recovery" (27% with low emotional exhaustion and very high emotional thriving and emotional recovery). Nurses in the "exhausted" and "exhausted with thriving" profiles reported greater depression and poorer work‐life integration. Nurses in "exhausted" profile were more likely to work in an inpatient setting. Nurses in the "exhausted with thriving and recovery" and "thriving and recovery" profiles reported more positive emotions, more well‐being behaviours, and better work‐life integration, with the "thriving and recovery" subgroup having the highest levels of these characteristics, lower depression scores and greater racial minority representation. Conclusion Approaches designed to improve nurse well‐being should be tailored to the nurses' profile of emotional exhaustion, thriving and recovery to maximize effectiveness. Impact Given the growing shortage of nurses in healthcare systems, it is critical that multilevel strategies be investigated to retain nursing staff that consider the intersectionality and complexity of the different aspects of burnout and resilience experienced by the nurse. No Patient or Public Contribution The aim was to assess burnout and resilience among nurses.